ANALISIS IMPLEMENTASI KEUANGAN BERKELANJUTAN TERHADAP PROFITABILITAS BANK - Fourinda, Nilna Elminah; Nurman Setiawan Fadjar (Contemporary Studies in Economic, Finance and Banking, 2024)
In practice, banks must maintain business continuity by paying attention to their profitability. However, in response to global issues related to sustainable development goals, banks are also obliged to direct their business towards sustainability by implementing sustainable finance. This study aims to further analyze how the implementation of sustainable finance, particularly sustainable lending and the realization of Environmental Social Responsibility (CSR) funds, can affect bank profitability. Economic sustainability theory emphasizes the importance of balance between economic, social, and environmental aspects. This study uses the panel data regression analysis method. The implementation of sustainable finance proxied by sustainable credit has a significant positive effect on bank profitability, while the realization of CSR funds has a significant negative effect on bank profitability. This research is expected to provide a more comprehensive insight into how banks can balance social responsibility and environmental sustainability with the need to maintain healthy profitability.